Medical Oncology Workload in Europe: One Continent, Several Worlds. Issue 1 (January 2020) - Seruga, B.; Sullivan, R.; Fundytus, A.; Hopman, W.M.; Ocana, A.; Joffe, J.; Bodoky, G.; Le Tourneau, C.; Vanderpuye, V.; Lopes, G.; Hammad, N.; Sengar, M.; et al.
Abstract: Aims: The workload pressure on medical oncologists will increase in the near future. There are no comprehensive data available about the current workload of medical oncologists in Europe. Here we report the European results of a global survey of the workload of medical oncologists. Materials and methods: An online survey was distributed through a snowball method via national oncology societies to chemotherapy-prescribing physicians in 21 European countries. We compared the workload of medical oncologists in Eastern European countries (EECs) and Western European countries (WECs). The primary measure of workload was the annual number of new cancer patient consults seen per oncologist. Results: In total, 495 oncologists from 16 European countries completed our survey: 100 from seven EECs and 395 from nine WECs. The median number of annual consults per medical oncologist was 225 in EECs compared with 175 in WECs ( P  < 0.001). The proportion of medical oncologists seeing more than 300 consults/year was 35% (35/100) in EECs compared with 18% (68/395) in WECs. The median number of patients seen in a full day clinic was 25 in EECs and 15 in WECs ( P  < 0.001). Eastern European medical oncologists reported spending a median of 25 min per new consultation compared with 45 min in WECs ( P  < 0.001). The top two reported barriers in both EECs and WECs to patient care were high clinical volumes and insufficient time for reading. Conclusion: The clinical workload of medical oncologists in EECs was substantially higher than in WECs. European health policymakers and educators need to address existing disparities in the workload of medical oncologist, undertake plans for future workforce supply and consider alternative models of care. Highlights: This study offers high-level insight into medical oncology workload and delivery of clinical cancer care in Europe. A substantial proportion of medical oncologists exceeds recommended workload targets. Clinical workload of medical oncologists in Eastern Europe is substantially higher than in Western Europe.